Effects of seismogenic width and low-velocity zones on estimating slip-weakening distance from near-fault ground deformation - Chen, Xiang; Yang, Hongfeng (Geophysical journal international, 2020)
SUMMARY Fault weakening process controls earthquake rupture propagation and is of great significance to impact the final earthquake size and seismic hazard. Critical slip-weakening distance (${D_c}$) is one of the key parameters, which however is of difficult endeavours to be determined on natural faults, mainly due to its strong trade-off with the fault strength drop. An estimation method of ${D_c}$ proposed by Fukuyama et al. provides a simple and direct reference of ${D_c}$ on real faults from the near-fault ground displacement at the peak of ground velocity (${D_c}^{′′}$). However, multiple factors may affect the observed near-fault ground velocity and thus need to be considered when estimating ${D_c}.$ In this work we conduct 3-D finite element numerical simulations to examine the effects of finite seismogenic width and near-fault low velocity zones (LVZs) on the results of ${D_c}^{′′}$. In uniform models with constant prescribed ${D_c}$, the derived ${D_c}^{′′}$ values increase with seismogenic width. Furthermore, the scaling between ${D_c}^{′′}$ and final slip in models with a constant ${D_c}$ indicates that the scale-dependent feature of ${D_c}^{′′}$ might not be related to variation in friction properties. With a near-fault LVZ, ${D_c}^{′′}$ values show significant magnification. The width of the LVZ plays a more important role in enlarging ${D_c}$ estimation compared to the depth of the LVZ. Complex wavefields and multiple wiggles introduced by the LVZ could lead to delay pick and then cause large deviation. The value of ${D_c}$ on the fault may be overestimated through ${D_c}^{′′}$ from limited stations only.